Map-based Cloning and Characterization of the BPH18 Gene from Wild Rice Conferring Resistance to Brown Planthopper (BPH) Insect Pest - Ji, Hyeonso; Kim, Sung-Ryul; Kim, Yul-Ho; Suh, Jung-Pil; Park, Hyang-Mi; Sreenivasulu, Nese; Misra, Gopal; Kim, Suk-Man; Hechanova, Sherry Lou; Kim, Hakbum; Lee, Gang-Seob; Yoon, Ung-Han; et al. (Springer, 2016)
Brown planthopper (BPH) is a phloem sap-sucking insect pest of rice which causes severe yield loss. We cloned the BPH18 gene from the BPH-resistant introgression line derived from the wild rice species Oryza australiensis. Map-based cloning and complementation test revealed that the BPH18 encodes CC-NBS-NBS-LRR protein. BPH18 has two NBS domains, unlike the typical NBS-LRR proteins. The BPH18 promoter